The Problem of the Features of Modern Science - Mikailova, Narmina (Scholarya Demo Journal of Ruby, 2020)
The main task of modern philosophy of science is to develop an adequate model of the structure of real science and the laws of its development, to build a rational and theoretical form of people’s worldview. The concept of modern philosophy of science is based on the idea of the relationship between philosophy and science and the understanding of the inconsistency and complexity of the laws of development and structure of science. The fundamental question of philosophical epistemology is the question of the unity of theory and practice in the process of obtaining truth. Practice is of decisive importance in the development of science. A person actively influences the environment, and in the course of change learns it. Practice and cognition are two interrelated aspects of a single historical process where practice plays a decisive role. Only developing practice can be the basis and criterion of developing objective knowledge. The practical orientation of modern science is expressed in an increase in the number of applied research and development, as well as in the application of science in the field of civil economy and in meeting the growing needs of people and society. Scientific knowledge includes four levels: sensory, empirical, theoretical and metatheoretical. They are internally interconnected in the process of functioning and development of scientific knowledge. The theoretical level of scientific knowledge is a complex psychological and creative process. The elements of creativity are manifested to the greatest extent in the mechanisms of scientific discoveries and scientific revolutions. An important feature of modern science is the social and collective nature of scientific activity. This is evidenced not only by its social organization, but also by the manifestation of the sociality of scientific knowledge, such as rivalry in any of the sciences of its various research programs, theories, scientific schools, funding, etc. Modern science also plays a role in solving global problems of mankind; in this regard, the principle of responsibility and the ethos of a scientist occupies a key place. Strengthening external influences on modern status makes modern science an object of social study. Modern science is a professional activity related to the basic interests of society and the state, its significance goes beyond the framework of epistemology and claims to determine a special disciplinary status.